Development of muscle strength in physical education classes (Journal of Pedagogical Inventions and Practices, 2023)
In sports, it is impossible to perform movements using only one muscle. Many muscles or muscle groups are involved in solving any movement problem. The potential base of strength consists mainly of cross-sectional muscle tissue, muscle size, muscle structure and intra-muscular coordination. This also means that the nervous system focuses on the use of muscles to solve specific movement tasks. This article provides information about ways to develop the strength of different groups of muscles.